Struggling with Jazz - DeVeaux, Scott (Current Musicology, 2001)
As a musicologist, I'm accustomed to forming opinions that nobody in particular wants to hear. So when Ken Burns's mega-documentary Jazz first aired on PBS in January 2001, it was an interesting time to be an aca-demic specialist in jazz. Suddenly everyone, from close friends to casual acquaintances, was asking what I thought, and a surprising number actually wanted to hear the answers.